Playing with Failure. Conceptualization of Failure in Game Studies - Kozyra, Magdalena (Replay. The Polish Journal of Game Studies, 2019)
The aim of the article is to present examples of already existing theories about the experience of failure in digital games and then propose a different approach to it. Firstly, it shows the way Csíkszentmihályi’s flow theory and Juul’s The Art of failure describe the motivational role of failure; then it points out the persuasive aspects of Bogost’s rhetoric of failure used in serious games industry; and lastly Lee’s, Roche’s and Halberstam’s approaches trying to recognize the positive features of failure are examined. The author then introduces six dimensions of failure based on Calleja’s Player Involvement Model. Through them, an alternative way of thinking about failure is proposed, in which the failure is perceived not (only) as an occurrence which needs fixing, but as a possibility for a different experience of gameplay.